Chemical and electrical impact of lightning on the Earth mesosphere: The case of sprite halos. Issue 8 (1st August 2013) - Parra‒Rojas, F. C.; Luque, A.; Gordillo‒Vázquez, F. J.
Abstract : [1] A one‒dimensional electrochemical model is developed to describe, in a self‒consistent way, the response of the Earth mesosphere to different types of lightning discharges between 50 and 87 km of altitude. This model is applied to the case of sprite halos, one of the most common types of transient luminous events (TLE). We have studied the time‒altitude evolution of more than 20 chemical species. Our model predicts an increase of up to 70 cm −3 in the electron density from ambient electron density values between 55 and 81 km of altitude in the +CG lightning cases and a negligible mesospheric electron density perturbation in the −CG lightning case. For all the +CG and some −CG (200 kAkm) cases considered, the model also shows an enhancement of several orders of magnitude in the concentration of ground‒state negative ( O −, O 2 −, NO 2 − ) and positive ( O 2 +, O 4 + ) ions and electronically excited positive ions such as N 2 + ( A 2 Π u ) responsible for the N 2 + Meinel emissions and N 2 + ( B 2 Σ u + ) . On the other hand, for the first positive group of N2 the calculated emission brightness exceeds the threshold of visibility (1 MR) for a halo of 100 km of diameter at an altitude of 77 km for all the CG lightning discharges studied (except for the −CG case with 100 kAkm current peak) and for relatively lower altitudes when +CG lightnings are considered. Moreover, the calculated concentration of the metastables N 2 ( A 3 Σ u + ) and O( 1 D) exhibit an enormous enhancement (of more than 10 orders of magnitude) over their ambient values that, for +CG, remains high (5–7 orders of magnitude above ambient values) for long times (up to 500 s), below 55 km. Key Points: Electrochemical impact of CG produced halos in the mesosphere is calculated. The calculated concentration of metastables exhibits a significant enhancement. The model predicts a sharp increase in the electron concentration above 55 km.